2018
DOI: 10.3996/122017-jfwm-099
|View full text |Cite
|
Sign up to set email alerts
|

Propylene Glycol in Free-Ranging Green Sea Turtle Plasma

Abstract: Metabolomics is the study of metabolites, the small-molecular-weight end products of metabolism. Propylene glycol is a synthetic diol commonly used as antifreeze, as a humectant, and in the production of polyester compounds. In otherwise healthy animals, propylene glycol has generally been considered a contaminant, iatrogenic, or unexplained. We demonstrate the presence of propylene glycol in plasma of free-ranging apparently healthy green sea turtles Chelonia mydas and individuals impacted by cold stun syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This metabolite may be of bacterial or yeast origin (Enebo 1954, Suzuki and Onishi 1968), made biogenically by the turtles (Saxena et al 2010), or an environmental contaminant. If a true metabolite, the turtles could be using it to provide energy and protect against ketosis through gluconeogenesis, the carboxylic acid cycle and glycogenesis (Shull and Miller 1960, Ruddick 1972, Morshed et al 1988, Nielsen and Ingvartsen 2004) or potentially as a cryoprotectant (Niemuth et al 2018). We do not have an explanation for the observed species difference.…”
Section: Discussionmentioning
confidence: 99%
“…This metabolite may be of bacterial or yeast origin (Enebo 1954, Suzuki and Onishi 1968), made biogenically by the turtles (Saxena et al 2010), or an environmental contaminant. If a true metabolite, the turtles could be using it to provide energy and protect against ketosis through gluconeogenesis, the carboxylic acid cycle and glycogenesis (Shull and Miller 1960, Ruddick 1972, Morshed et al 1988, Nielsen and Ingvartsen 2004) or potentially as a cryoprotectant (Niemuth et al 2018). We do not have an explanation for the observed species difference.…”
Section: Discussionmentioning
confidence: 99%
“…In several species of Lactobacillus , propylene glycol was produced through degradation of lactate under anaerobic conditions (reviewed by [ 57 ]). In our laboratory, we have found propylene glycol in other sea turtle samples while ruling out sources of sample and processing contamination [ 58 ]. This suggests that the propylene glycol is endogenously produced, derived from bacterial production in the gastrointestinal tract of sea turtles, or that it is obtained by the hatchlings from their environment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Soaudy et al (2021) have shown that inclusion of PG in the diet of Nile tilapia enhanced growth performance and feed utilization under cold stress (Soaudy et al 2021). Niemuth et al (2018) demonstrated the presence of PG in plasma of free-ranging sea turtles (Chelonia mydas) and suggested that this turtle species may be able to synthesize PG through reduction of glycerol, another important antifreeze compound (Niemuth et al 2018). Several studies have pointed to glycerol as a cryoprotectant and important metabolite for cold adaptation in the hibernating black bear and in the arctic insect Gynaephora groenlandica (Ahlquist et al 1984;Kukal et al 1988).…”
Section: Metabolomics Analysismentioning
confidence: 99%
“…The analysis of blood plasma and serum by 1 H NMR metabolomics has proven to be a remarkable screening method in human diagnostic medicine (Emwas et al 2013;Erben et al 2018;Powell et al 2018) and for investigating important clinical conditions, such as cancer (Giskeødegård et al 2018;Lima et al 2018;Spratlin et al 2009), diabetes (Lanza et al 2010) and Parkinson's disease (Pizarro et al 2019). While NMR metabolomics applications in human health and medical sciences continue to feature numerous high quality research, the powerful analytical potential of 1 H NMR spectroscopy has led to the expansion of bloodbased metabolomics applications also to the veterinarian and animal breeding (livestock and aquaculture) fields (Başoǧlu et al 2014;Bertram et al 2006;Bin et al 2018;Dove et al 2012;Jones & Cheung, 2007;Le Moyec et al 2014;Luck et al 2015;Niemuth et al 2018;Shestakova et al 2018;Ziarrusta et al 2018). In particular, 1 H NMR metabolomics is establishing itself as an important tool for the assessment of the most relevant issues in the aquaculture industry, including fish health and alternative feed development (Alfaro & Young, 2018;Young & Alfaro, 2016).…”
Section: Introductionmentioning
confidence: 99%